Political authority and spectral stories from the margin in Shakespeare's Hamlet, Oğuz Atay's The Disconnected and Tom Stoppard's Rosencrantz and Guildenstern are Dead - Şentürk, Neslihan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2013., 2013)
This thesis is an attempt to explore ways in which political authority manipulates narratives about the past. It also analyzes how literature can be a site of the spectral through which counter-histories of those who are marginalized and overshadowed by dominant narratives in a society are written. Drawing centrally upon the figure of the ghost in Shakespeare‟s Hamlet, I explore the role of the spectral in two texts: The Disconnected (1972) by the Turkish novelist Oğuz Atay, and Rosencrantz and Guildenstern are Dead (1966) by the English playwright Tom Stoppard. I begin by analyzing the relationship between collective memory, amnesia and trauma. I then examine the rise of the spectral in the Atay and Stoppard texts, with special emphasis on their social and political contexts. I argue that specters in these texts offer points of resistance that enable the production of counter-narratives pertaining to the past. This resistance comes in the form of the figurative language of literature, which is relatively less influenced by power relations and the manipulative potential of language in societies.